Peningkatan Skrining Hipertensi Remaja melalui Program "GEBRAK SEKOLAH CERDIK" UPTD Puskesmas Kuningan - Azrafy Salsya; Risna Nurlia; Enung Nur’Aisah; Ida Farida (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The problem of low hypertension screening coverage among vocational high school (SMK) students in the UPTD Puskesmas Kuningan area only reached 69.7%. The applied community service methods included public education and cadre empowerment through the innovative "GEBRAK SEKOLAH CERDIK" program. This activity aimed to resolve the complex issue of low hypertension screening. Program implementation involved interactive health education, task-shifting training for School Health Effort (UKS) teachers and Youth Health Cadres (KKR), alongside medical record digitalization using the Sehat Indonesiaku Application (ASIK) portal for over 400 tenth-grade students at SMK Pertiwi Kuningan. Results indicated increased student health literacy regarding asymptomatic hypertension prevention and the CERDIK healthy lifestyle. Involving KKR as peer examiners and adopting digital applications proved highly effective in reducing bureaucratic inefficiency and overcoming medical personnel shortages. In conclusion, replicating this school empowerment model is crucial to independently optimize the early detection of non-communicable diseases among adolescents.